Pengaruh Akuntabilitas, Budaya Organisasi, Ethical Leadership, Dan Motivasi Terhadap Kinerja Karyawan(Studi Empiris Pada PT. Infiltraco Murni Serang Banten) - Wulandari, Tri Ayu; , Dr. Noer Sasongko, S.E., M.Si., AK., CA (2017)
This research aims to analyze the Influence Accountability, Cultural Organization, Ethical Leadership and Motivation on Employee Performance (Empirical Study at PT. Infiltraco Pure Serang Banten). The sampel in this study were all employees of PT. Infiltraco Murni Serang Banten totaling 63 people using a survey approach. The sampling method used in this research is non probability that the convenience sampling. The data used in this research using primary data. Data collection techniques were taken directly by using a questionnaire. The analysis tool used is multiple linear regression. The result of this research showed that accountability, ethical leadership, and motivation affect the performance of employees, but the organizational culture didn't affect the performance of employees.